Free-form catenary-inspired meta-couplers for ultra-high or broadband vertical coupling - Chen Tianqu; Xu Mingfeng; Pu Mingbo; Tang Xi; Zheng Yuhan; Zeng Qingji; Xiao Yuting; Ha Yingli; Guo Yinghui; Zhang Fei; Chi Nan; Luo Xiangang (Nanophotonics)
Metasurface-assisted waveguide couplers, or meta-couplers, innovatively link free-space optics with on-chip devices, offering flexibility for polarization and wavelength (de)multiplexing, mode-selective coupling, and guided mode manipulation. However, conventional meta-couplers still face challenges with low coupling efficiency and narrow bandwidth due to critical near-field coupling caused by waveguide constraints and unit-cell–based design approach, which cannot be accurately addressed using traditional design methods. In this paper, quasi-continuous dielectric catenary arrays are first employed to enhance efficiency and bandwidth by addressing adjacent coupling issues of discrete metasurface. Then, diffraction analysis demonstrates that the performance of forward-designed couplers is hindered by spurious diffraction orders and destructive interference. To further enhance performance, an adjoint-based topology optimization algorithm is utilized to customize electric near-field, which can effectively suppress spurious diffraction orders and destructive near-field interference, achieving ultra-high coupling efficiency of 93 % with 16.7 dB extinction ratios at 1,550 nm. Additionally, a broadband meta-coupler exceeds 350 nm bandwidth with 50 % average coupling efficiency across O- to L-bands using multiobjective optimization. These high-performance devices may render them suitable for applications in optical communications, sensing, and nonlinear optics. Moreover, the inverse design method shows potential for improving the performance of various metasurface-integrated on-chip devices.